1991
DOI: 10.3354/meps072079
|View full text |Cite
|
Sign up to set email alerts
|

Phenology in Calanus finmarchicus; hypotheses about control mechanisms

Abstract: Calanus finmarchicus (Gunnerus) stratify nariowly near 500 m depth dunng their fifth copepodite resting phase in North Atlantic Slope Water off southern New England USA They probably a c h~e v e this by migration to a specific, daytime isolume Photoperiod information provided by light intensity at depth could serve as a cue for termination of the resting phase Population data on tooth formation and gonad growth show that the reshng stock prepares foi termination in late winter and matures in February-March Pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
114
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(117 citation statements)
references
References 38 publications
1
114
1
Order By: Relevance
“…Diapause in C. finmarchicus is identified by a combination of classic behavioral, morphological, and biochemical characteristics: diapausing C5 copepodids accumulate at depths below 200 to 300 m in oceanic waters (Heath et al, 2004;Miller et al, 1991;Sameoto and Herman, 1990), have empty guts with thin epithelia (Bonnet et al, 2007;Hirche, 1983), and have large oil sacs (Miller et al 2000). Indicative of arrested development, diapausing copepods have reduced transcriptional activity (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diapause in C. finmarchicus is identified by a combination of classic behavioral, morphological, and biochemical characteristics: diapausing C5 copepodids accumulate at depths below 200 to 300 m in oceanic waters (Heath et al, 2004;Miller et al, 1991;Sameoto and Herman, 1990), have empty guts with thin epithelia (Bonnet et al, 2007;Hirche, 1983), and have large oil sacs (Miller et al 2000). Indicative of arrested development, diapausing copepods have reduced transcriptional activity (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…low RNA:DNA ratios) (Wagner et al, 1998), low ecdysteroid levels (Johnson, 2004), and delayed molt progression (i.e. cessation of tooth formation) (Miller et al, 1991). Molecular markers of diapause include low expression of genes related to lipid synthesis, transport, and storage (ELOV, FABP, RDH) and high expression of ferritin and ecdysteroid receptor (EcR) in diapausing copepods (Tarrant et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, change in total lipid content of only a few percentage points can make a significant difference to the buoyancy properties of the animal. Only a small percentage of the stored lipids are consumed during overwintering (Hagen and SchnackSchiel 1996; Jó nasdó ttir 1999), but since development, maturation, fertilization, and arousal from the resting phase often start at overwintering depth before rising to the surface (Miller et al 1991;Schnack-Schiel et al 1991;Atkinson et al 1997), biochemical composition does change.…”
mentioning
confidence: 99%
“…These hypotheses may also explain emergence mechanisms in other species and other environments as well. Another proposed hypothesis is the seasonal change in day length (Miller et al 1991;Fisken 2000), but this hypothesis is unlikely to be the case for C. carinatus in the tropical Indian and Atlantic Oceans, where this species is found, because the seasonal change in day length is negligible. Although ocean currents determine the dispersal and fate of the diapaused copepods, the majority of individuals successfully completing their life cycles were those retained within the coastal zone.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally believed that the mechanism controlling diapause is a combination of internal cues in the form of a timing mechanism, such as endocrine titer levels or critical lipid content, and external cues such as a shift in the light environment (Miller et al 1991;Hirche 1996). Miller et al (1991) speculated that light intensity (or possibly daylength) is the critical factor that determines emergence of copepods from diapause. These authors suggested that increased light intensity triggered by physical uplift of the diapausing copepods onto the continental shelf is the primary mechanism terminating diapause in Calanoides carinatus off the east and west coasts of Africa.…”
mentioning
confidence: 99%